2020
DOI: 10.3390/brainsci11010018
|View full text |Cite
|
Sign up to set email alerts
|

Trait-Based Dimensions Discriminating Adults with Attention Deficit Hyperactivity Disorder (ADHD), Autism Spectrum Disorder (ASD) and, Co-occurring ADHD/ASD

Abstract: This study assessed the co-occurrence of attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) in newly diagnosed adults of normal intelligence and the contribution of trait-based dimensions deriving from the Barkley Adult ADHD Rating Scale-IV (BAARS-IV), the Autism-Spectrum Quotient (AQ), and the Empathy Quotient (EQ) to the differentiation of patients with ADHD, ASD, and ADHD/ASD. A total of 16.1% of patients with ADHD received a co-occurring ASD diagnosis, while 33.3% of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 70 publications
(90 reference statements)
3
16
0
Order By: Relevance
“…Moreover, the present study supports the previous findings about higher AQ and lower EQ in individuals with ASD compared to healthy individuals [16]. EQ was designed to measure empathic abilities, which refer to how easily a person perceives the feelings of others and is affected by their emotions [50]. Some argue that low empathic abilities are particularly important in understanding a person's social adjustment challenges and are important factors in psychiatric diagnoses with adults [51].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, the present study supports the previous findings about higher AQ and lower EQ in individuals with ASD compared to healthy individuals [16]. EQ was designed to measure empathic abilities, which refer to how easily a person perceives the feelings of others and is affected by their emotions [50]. Some argue that low empathic abilities are particularly important in understanding a person's social adjustment challenges and are important factors in psychiatric diagnoses with adults [51].…”
Section: Discussionsupporting
confidence: 89%
“…Some argue that low empathic abilities are particularly important in understanding a person's social adjustment challenges and are important factors in psychiatric diagnoses with adults [51]. According to research on adults with neurodevelopmental disorders [50], the EQ scores of ASD patients and of those with both diagnoses of ASD and attention deficit hyperactivity disorder (ADHD) are lower than ADHD patients, suggesting that low EQ indicates a single diagnosis or co-occurrence of ASD. However, no significant differences were found between the groups in terms of SQ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in our sample, children with ASD+ did not score significantly higher than children with ASD alone. A recent study by Pehlivanidis et al (2021) reported similar findings at the AQ, showing that adults with ASD+ and ASD− had comparable scores, in turn significantly higher than the ADHD group. It means that the effect of comorbid ADHD seemed not to be additive in the reported severity of ASD and the reasons should be examined in future studies.…”
Section: Discussionsupporting
confidence: 62%
“…The subscales that were finally used for the statistical analyses were the following: attention deficit (0 to 9 points), hyperactivity (0 to 5 points) and impulsivity (0 to 4 points), as used in previous studies. 37 The suggested cut-off scores for each subscale were not taken into consideration and the scale was treated as dimensional and not categorical since the assessed traits don't provide a diagnosis. 37 The alpha coefficient was 0.95 in the current study.…”
Section: Barkley Adult Adhd Rating Scalementioning
confidence: 99%